Validation of a booklet on self-care with the diabetic foot - Yara Lanne Santiago Galdino; Thereza Maria Magalhães Moreira; Antonio Dean Barbosa Marques; Francisca Alexandra Araújo da Silva
ABSTRACT Objective: to describe the validation of the booklet on self-care with the feet of people with diabetes. Method: methodological study, focusing on the validation of a printed booklet. The content and appearance of the booklet was validated by 23 judges divided into three groups: 11 content and appearance, seven technicians and five of the area of design and marketing. The appearance was validated by 30 people with type 2 Diabetes Mellitus. Results: the judges in the nursing area allowed the validation of material with a Content Validity Index (CVI) of 0.99, judges in the area of design and marketing with Suitability Assessment of Materials (SAM) of 99.2% and the target audience with concordance index of 99.4%. Conclusion: the educational booklet proved to be valid and reliable educational material to be used in order to promote compliance with self-care with the feet of people with Diabetes Mellitus.